Chicken soup for the soul : hope & healing for your breast cancer journey : surviving and thriving during and after your diagnosis and treatment - Silver, J. K. 1965- (Chicken Soup for the Soul Health, 2012)
A collection of stories for breast cancer patients accompanied by medical text, covering how patients can best handle the diagnosis, assembling their medical teams, creating a support network among family and friends, managing their way through the treatment and the rehab and recovery that follow, and handling the reality of being a cancer survivor in the long term.